Estudo fitoquímico da espécie Piper mollicomum Kunth e atividade antibacteriana - Leite, Fernando Ferreira (2019)
The genus Piper is considered the largest of the family Piperaceae. With more than 2000 species already described, it is found mainly in tropical and neotropical regions. It has a high commercial value for its wide use in both popular medicine and traditional cuisine, becoming the target of several researches. They have a differentiated metabolism, producing classes of substances that are not usually found as alcamides aristolactamas, aporfínicos alkaloids and kavalactonas, increasing even more its therapeutic potential. Among the species of the genus Piper are Piper mollicomum Kunth, popularly known as jaborandi or jaborandi-meso, and in this work, chemical investigations were carried out with their roots that were collected in campus I of the Federal University of Paraíba, municipality of João Pessoa- PB. The methanolic extracts were subjected to conventional chromatography (silica gel adsorption and XAD-2 and dextran gel exclusion) resulting, after physical (melting point) and spectrometric (Infrared Spectrometry and Nuclear Magnetic Resonance 1H and 13C, including uni and bidimensional techniques) in four substances identified as two aristolactams - 10-Methylamine-4-hydroxy-2,3-dimethoxyphenanthren-1carboxylic acid-lactam and 10-methylamine-4-hydroxy -3-methoxyphenanthren-1carboxylic acid-lactam, in addition to an acid identified as 3,4,5-trimethoxyphenyl propanoic acid and an isobutyl amide identified as 2-Propenamide, 3- (6-methoxy1,3- benzodioxol-5-yl) -N- (2-methylpropyl) - (2E), the first 3 being reported for the first time in the species. The antimicrobial activity of these four substances in Grampositive bacteria (Bacillus subtilis CCT 0516; Staphylococcus aureus 47; Staphylococcus aureus ATCC8027; and Gram-negative strains (Escherichia coli 13, Escherichia coli ATCC 2536, Pseudomonas aeruginosa ATCC 8027, Pseudomonas aeruginosa 102), however none of them exhibited antibacterial activity since there was no inhibition of the growth of Gram-positive and Gram-negative strains tested.